Amide bond-containing monodisperse polyethylene glycols beyond 10 000 Da. Issue 33 (1st August 2016) - Wan, Zihong; Li, Yu; Bo, Shaowei; Gao, Ming; Wang, Xuemeng; Zeng, Kai; Tao, Xin; Li, Xuefei; Yang, Zhigang; Jiang, Zhong-Xing
Abstract : Monodisperse polyethylene glycols above 4000 Da, including the longest one to date (10 262 Da), can be prepared from oligoethylene glycol-containing ω-amino acids through solid phase synthesis. Abstract : Although monodisperse polyethylene glycols (M-PEGs) above 4000 Da are especially valuable in biomedical applications, their synthesis remains a long-standing challenge. To this end, a peptide-based strategy for such M-PEGs was developed. With macrocyclic sulfates as the key intermediates, a panel of oligoethylene glycol (OEG) containing ω-amino acids were prepared with high efficiency. Through solid phase peptide synthesis (SPPS), these amino acids were conveniently assembled into a series of amide bond-containing M-PEGs with high flexibility in molecular weight and amide density selection. With this strategy, an M-PEG of 10 262 Da was prepared on a gram scale and its biocompatibility was assessed in a mice model.